The Philanthropy of Coastal Society: The Challenge and Strategy of Komunitas Jumat Berkah Muara Pantuan - Fredy Torang Widiyanto Munthe (Lentera: Jurnal Ilmu Dakwah dan Komunikasi, 2022)
The philanthropic activities undertaken by various nonformal religious organizations in Indonesia have been experiencing significant growth. One such organization is the Komunitas Jumat Berkah Muara Pantauan (KJBMP). This study aims to examine the strategies employed by KJBMP in conducting philanthropic efforts within the coastal community of Muara Pantauan, East Kalimantan, and to identify any obstacles encountered in implementing these strategies. This research employs a descriptive-qualitative methodology, utilizing in-depth interviews with KJBMP administrators. The author also participated in one year of participatory observations within the Muara Pantauan coastal community. Data were analyzed using a thematic approach based on Anheir's concept of charitable philanthropy categorization. Findings indicate that KJBMP utilizes a charitable strategy in its philanthropic efforts in the Muara Pantauan coastal region. However, KJBMP has also recently begun implementing economic development strategies to promote self-sufficiency promote self-sufficiency within the disadvantaged community of Muara Pantauan.